Combined experimental and numerical analysis of critical loading conditions for hard metal tool damage in titanium milling. (May 2022) - Kaltenbrunner, T.; Maier, K.; Klünsner, T.; Krückl, H.P.; Krobath, M.; Pötz, M.; Wosik, J.; Binder, O.; Teppernegg, T.; Czettl, C.; Ecker, W.
Abstract: The present work investigates an indexed cutter with round cutting inserts manufactured from hard metal grade M10 with 10 wt% Co binder and WC grain size of 2 μm used for the application of milling the titanium alloy Ti-6Al-4V. The focus is set on the cyclic thermomechanical loading in combination with tool degradation. For this sake, a combined 2D and 3D finite element modelling approach is introduced in order to determine the thermal and mechanical tool loading locally resolved and to reveal the specifics of a round cutting insert geometry. The finite element model allows establishing the linkage between the material damage observed in uniaxially loaded laboratory specimens with real tool degradation observed in cutting experiments for the calculated critical loading conditions. For the investigated round insert with 10 mm diameter applied in a cutting operation with 55 m min −1 cutting speed and 0.125 mm feed per tooth, a maximum cutting edge temperature between 600 °C and 700 °C and stress amplitudes between 1500MPa and 2000 MPa at a stress ratio R σ  < − 4 are calculated. This loading is close to the load limit for cavity formation and accumulation in M10 which for the temperature of 700 ° C and a stress ratio R σ  = − ∞ was experimentally found to be at a stress range of 1500 MPa. This reveals that the investigated process conditions are close to the limit of safe tool application which is in accordance with findings from cutting tests. The presented approach provides a novel and highly valuable method for future tool material and cutting process development and research. Graphical abstract: Unlabelled Image Highlights: Efficient high resolution 2D-3D modelling approach for round milling inserts Local cutting edge loading in limit load case for Ti6Al4V milling quantified High temperature fatigue test shows similar damage evolution as in-service. A round geometry makes cuttings inserts comb crack resistant.